The Effect of Religiosity and Ethical Orientation on Perceptions of Undergraduate Accounting Students on Creative Accounting (Department of Accounting, Faculty of Economics, Universitas Negeri Semarang, 2020)
The purpose of this research is to determine the effect of religiosity and ethical orientation on the perception of creative accounting. The sampling technique used was purposive sampling technique. Students who participated as respondents were as many as 107 students from Universitas Negeri Yogyakarta and 249 students from Universitas Islam Indonesia who were then grouped based on criteria. The criteria used are already or are currently taking intermediate financial accounting 1 and intermediate financial accounting 2 courses, auditing courses, and business ethics courses. Based on the predetermined criteria, a sample of 202 students was obtained consisting of 98 Universitas Negeri Yogayakarta students and 104 Universitas Islam Indonesia students. The students involved in this study were given a questionnaire to fill in and the data obtained were analyzed using multiple regression methods. The results of this study indicate that there is an effect of religiosity on students’ ethical perceptions in creative accounting. The students with high religiosity will have perceptions that are more ethical on creative accounting. The results of the analysis also show that ethical orientation has an effect on creative accounting. This means that the higher the ethical orientation of students, the more ethical their perceptions of creative accounting are.